Factors Supporting Turkey’s Policy to Purchase Russian S-400 Anti-Air Strike Defense Units - Jamila, Maryam; Yonanda, Chendika; Harza, Zulkifli; Masri, Ilman Syarif (Journal of Strategic and Global Studies, 2020)
Turkey is a member of the NATO military alliance since 1952, as a member of NATO, cooperation between Turkey and Russia invites counterparts from other NATO alliance countries. But even with criticism, Turkey continues purchasing S-400 from Russia . Therefore, this study aims to analyze the factors that support Turkey's policy on purchasing S-400.This research is a descriptive research through internet-based literature.Turkey's policy in purchasing S-400 analyzed using the concepts of Arms, Alliances and Security Tradeoffs proposed by James D. Morrow. James stated that there are three factors that influence the state to conduct arming; economic & military technological factors, the lack of alliances effectiveness and differences in national interests between alliances.This study found that all of these factors occurred in the conditions of Turkey and NATO. With fulfillment of these three factors, Turkey chose to do arming instead of alliancing in facing national threat